Analisis Perbedaan Volume Material Antara Metode Truck Count dan Mine Survey pada Kegiatan Penambangan Terbuka (Studi Kasus Pit Lokma PT. Serinding Sumber Makmur, Kalimantan Barat) - Setiani, Dewi Nur; MS, Murad; Aprillia, Ricka (Universitas Tanjungpura, 2026)
PT. Serinding Sumber Makmur (PT. SSM) is a gold mining company operating an open-pit system in Ketapang Regency, West Kalimantan. In practice, discrepancies are often found between material volume calculations using the Truck Count and Mine Survey methods, which can affect production targets and gold recovery levels. This study aims to evaluate the volume differences between the two methods at Pit Lokma of PT. SSM and to identify the contributing factors. The research analyzed ore and overburden volumes for June 2025 using both methods. Results show that the Truck Count method recorded 30,929.47 BCM, while the Mine Survey method measured 33,759.94 BCM. The difference of 2,830.47 BCM resulted in a deviation of 8.38%, exceeding the ASTM tolerance (±2.78%) but still within the company’s internal standard (90% ≤ x ≤ 110%), with a value of 109.15%. Key factors contributing to the deviation include variations in dump truck loads, hauling road conditions during rainfall, material hardness, recording errors, and insufficient survey point density. Recommended improvements include load standardization, regular vessel capacity evaluation, better road maintenance, improved recording accuracy, and denser survey point measurements. These findings highlight the importance of integrating both methods with consistent technical control to enhance volume measurement accuracy and support optimal gold recovery.